46.8k views
4 votes
Solve for x 2(x - 2)² = (2x - 1)(x - 3)
answer please ​

2 Answers

6 votes

Answer: x = 5

Explanation:

Solve for x given the equation 2(x - 2)² = (2x - 1)(x - 3).

Simplify the equation.

2(x - 2)(x - 2) = (2x - 1)(x - 3)

2(x² - 4x + 4) = (2x² - 7x + 3)

2x² - 8x + 8 = 2x² - 7x + 3

Solve for x.

2x² - 8x + 8 = 2x² - 7x + 3

-8 - 8

2x² - 8x = 2x² - 7x - 5

+8x + 8x

2x² = 2x² + x - 5

-x - x

2x² - x = 2x² - 5

-2x² - 2x²

- x = - 5

- 5 ÷ - 1 = 5

x is equal to 5.

User Edwin Joassart
by
5.3k points
5 votes

Answer:

X = 5

Explanation:

User Jlunavtgrad
by
5.2k points